Nursing After Cerebrovascular Stroke - Darginavičienė, Daiva; Gedrimė, Lina (Slauga. Mokslas ir praktika, 2020)
Brain stroke is a medical emergency which ranks second in mortality and third in disability.According to the World Health Organization (WHO), as many as 80 percent of brain stroke patients die or remain disabled in middle and low-income countries such as Angola, Armenia, Moldova or Macedonia, etc. In the last four decades the number of brain strokes has more than doubled. Although medical world can witness great improvement in medical diagnostic technologies and attention to prevention and rehabilitation of brain strokes as well as public education, this medical condition remains one of the most important health problems both for the working people and elderly [1].The analysis of foreign scientific literature has also shown that much attention is paid to the general aspects of nursing patents after a brain stroke. However, there are no studies that quite accurately deal with the significance of nursing of patients after a brain stroke in hospital care.The aim of the research is to analyse nursing of patients who have experienced brain strokes.A quantitative research has been carried out which employed the anonymous written questionnaire survey prepared by the authors. The research was administered in Vilnius and Klaipeda health care institutions that provide tertiary multiprofile services. The study sample was constructed in a simple non-random manner and the data was processed using Microsoft Office Exel 2013. The research has been conducted in accordance with the principles of ethics.
Keywords: brain stroke; nursing; rehabilitation